Subcell Treatment of Sloped Interfaces between Debye Materials in the FDTD Method - Kenan Tekbas (Journal of Amasya University the Institute of Sciences and Technology)
This paper presents the application of the subcell technique for the treatment of sloped interface in finite-difference time-domain method. The technique is based on the averaging of permittivities in each cell crossed by the material interface. The frequency-dependent behaviour of materials was characterized using one-pole Debye model. The numerical experiment was conducted on the two-dimensional space.